The Influence of Digital - Based Strategic Management in Increasing Consumer Purchasing Interest - Astitiani, Ni Luh Putu Surya; Putra, I Gede Karang Komala; Widnyani, Ni Made (Global Health Science Group, 2024)
The study delves into exploring the impact of digital-based strategic management on consumer purchasing interest, particularly focusing on the local wisdom product